Elevated Levels of Insulin-Like Growth Factor (IGF)-I in Serum Rescue the Severe Growth Retardation of IGF-I Null Mice - Wu, YingJie (The Endocrine Society, 2009)
IGF-I plays a vital role in growth and development and acts in an endocrine and an autocrine/paracrine fashion. The purpose of the current study was to clarify whether elevated levels of IGF-I in serum can rescue the severe growth retardation and organ development and function of igf-I null mice. To address that, we overexpressed a rat igf-I transgene specifically in the liver of igf-I null mice. We found that in the total absence of tissue IGF-I, elevated levels of IGF-I in serum can support normal body size at puberty and after puberty but are insufficient to fully support the female reproductive system (evident by irregular estrous cycle, impaired development of ovarian corpus luteum, reduced number of uterine glands and endometrial hypoplasia, all leading to decreased number of pregnancies and litter size). We conclude that most autocrine/paracrine actions of IGF-I that determine organ growth and function can be compensated by elevated levels of endocrine IGF-I. However, in mice, full compensatory responses are evident later in development, suggesting that autocrine/paracrine IGF-I is critical for neonatal development. Furthermore, we show that tissue IGF-I is necessary for the development of the female reproductive system and cannot be compensated by elevated levels of serum IGF-I.